Eosinophils Methods and Protocols - Walsh, Garry M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2014)
In Eosinophils: Methods and Protocols, experts in the field of eosinophil biology comprehensively provide detailed methodological insight into the study of this fascinating cell. This book is aimed at a diverse range of basic and clinical scientists who wish to work with eosinophils or who require an update of their knowledge or to gain the information required to study a function of the eosinophil different to their current area of enquiry. Written in the highly successful Methods in Molecular Biology  series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, Eosinophils: Methods and Protocols seeks to aid scientist in the discovery of new hypotheses and  for further examination of this intriguing cell.
Eosinophil Overview - Structure, Biological Properties And Key Functions -- Eosinophil Purification From Peripheral Blood -- Eosinophil Purification From Human Bone Marrow -- CD34(+) Eosinophil-Lineage-Committed Cells In The Mouse Lung -- Eosinophil Cell Lines -- Cell Signalling In Eosinophil During Human Eosinophil Differentiation -- Eosinophil Intracellular Signalling – Apoptosis -- Identification Of Human Eosinophils In Whole Blood By Flow Cytometry -- Isolation And Functional Assessment Of Eosinophil Crystalloid Granules -- Eosinophil Chemotaxis -- Human Eosinophil Shape Change And Secretion -- Human Eosinophil Adhesion And Receptor Expression -- Adhesion Of Eosinophils To Endothelial Cells Or Substrates Under Flow Conditions -- Human Eosinophil Transmigration -- Measurement Of Eosinophil Kinetics In Healthy Volunteers -- Assays Of Eosinophil Apoptosis And Phagocytic Uptake -- Clinical Measurement Of Eosinophil Numbers In Eosinophilic Conjunctivitis -- Qualitative And Quantitative Studies Of Eosinophils In Parasitic Infections -- Interactions Of Eosinophils With Nerves -- Eosinophils Interaction With Mast Cells: The Allergic Effector Unit -- Eosinophil Interactions: Antigen Presentation -- Eosinophils And Respiratory Virus Infection: A Dual-Standard Curve Qrt-PCR-Based Method For Determining Virus Recovery From Mouse Lung Tissue -- Antimicrobial Activity Of Human Eosinophil Granule Proteins -- Eosinophils And The Ovalbumin Mouse Model Of Asthma -- Mutant Mice And Animal Models Of Allergic Disease -- Murine Models Of Eosinophilic Leukemia - A Model Of FIP1L1-PDGFRa Initiated Chronic Eosinophilic Leukemia/Systemic Mastocytosis.
Keywords: Immunology; Immunology